Complicated Staphylococcus aureus Bacteremia (SAB) Is Associated with Genetic Variation in GLS2. (4th October 2017) - Fowler, Vance; Ruffin, Felicia; Kuinkel, Batu Sharma; Cyr, Derek D; Guo, Shengru; Dykxhoorn, Derek; Skov, Robert; Bruun, Niels; Dahl, Anders; Lærke, Christian; Scott, William; Andersen, Paal; et al.
Abstract: Background: SAB is a serious, common infection. We used whole exome sequencing (WES) to examine the cumulative effect of coding variants in each gene on risk of complicated SAB in a discovery set of patients, and then evaluated the nominally significant genes in a replication set of patients using custom-capture sequencing. Methods: The discovery set comprised 84 complicated SAB cases (endocarditis or bone/joint infection) frequency-matched by age (in deciles), sex, and bacterial clonal complex (CC5/30, CC8) to 84 uncomplicated SAB controls. All were white inpatients at Duke University. WES utilized Agilent SureSelect 72Mb capture kits, followed by sequencing on an Illumina HiSeq2000, alignment and base calling with a standard pipeline. The SKAT-O and EPACTS packages were used for gene-based association tests and logistic regression models with Firth bias correction, respectively. Both controlled for age, sex, and clonal complex as covariates. The replication set of 122 complicated SAB cases and 118 uncomplicated SAB controls was frequency matched by age, sex, and clonal complex. All were white Europeans collected by the Statens Serum Institute. An Agilent SureSelect 2Mb capture array captured genic sequence for 342 genes nominally associated with complicated SAB in discovery (SKAT-O P < 0.035). Sequencing and data analysis proceeded as for WES. A Bonferroni-corrected gene-based test P -value of 1.5×10 – 4 determined significance in the replication set. Results: One gene, GLS2, was significantly associated with complicated SAB in the replication set ( P = 1.2 x 10 –4 ). The strongest single-variant association in all 342 genes was rs2657878 in GLS2 (p = 5×10 −4 ). This variant is strongly correlated with a missense variant (rs2657879, p = 4.4x10 -3 ) in which the minor allele (associated here with complicated SAB) has previously been shown to reduce circulating glutamine levels. Conclusion: Comprehensive examination of the coding sequence for association with complicated SAB in a two-stage discovery/replication design identified a novel candidate gene. GLS2 is an interesting candidate for complicated SAB due to its role in regulating glutamine production, a key factor in activation of T-cell production. Disclosures: V. Fowler Jr., Pfizer, Novartis, Galderma, Novadigm, Durata, Debiopharm, Genentech, Achaogen, Affinium, Medicines Co., Cerexa, Tetraphase, Trius, MedImmune, Bayer, Theravance, Cubist, Basilea, Affinergy, Janssen, xBiotech, Contrafect: Consultant, Consulting fee; NIH, Basilea, MedImmune, Cerexa/Forest/Actavis/Allergan, Pfizer, Advanced Liquid Logics, Theravance, Novartis, Cubist/Merck; Medical Biosurfaces; Locus; Affinergy; Contrafect; Karius: Grant Investigator, Research grant; Green Cross, Cubist, Cerexa, Durata, Theravance; Debiopharm: Consultant, Consulting fee; UpToDate: author on several chapters, Royalties